FINANCIAL ANALYSIS OF TILAPIA (O. niloticus) FRY BUSINESS ACTIVITY AT THE KLEMUNAN FISH FRY CENTER, BLITAR DISTRICT - ariadi - heri (Universitas Tidar, 2021)
Tilapia (O. niloticus) fish hatchery activity is a fishery business unit developed at the Klemunan Fish Fry Center (BBI), Blitar Regency. The purpose of this study was to determine the financial value and profit of the tilapia (O. niloticus) hatchery at the Klemunan Fish Fry Center (BBI), Blitar Regency. The research method used in this research is a survey research method with research data collection in 3 ways : active participation interviews, and observations. The financial analysis indicators analyzed are business profitability variables, R/C Ratio, Rentabilitas, Break Event Point (BEP) units and BEP sales. Based on the results of the financial analysis, the business profit value is Rp. 11.170.000,-, R/C Ratio at 8.81, BEP Unit at 58.6, BEP Sales Rp. 2,349,290, -, and business profitability of 49.9%, where the value of these indicators is very feasible because the numbers meet the criteria for a profitable business. So, from this research it can be concluded that based on business financial analysis which includes profitability analysis, R/C Ratio, BEP Unit, BEP Sales, and rantabilitas business, tilapia (O. niloticus) hatchery business activities at BBI Klemunan are very profitable and prospective to be developed.